2018
DOI: 10.3390/e20100727
|View full text |Cite
|
Sign up to set email alerts
|

Entropy, or Information, Unifies Ecology and Evolution and Beyond

Abstract: This article discusses how entropy/information methods are well-suited to analyzing and forecasting the four processes of innovation, transmission, movement, and adaptation, which are the common basis to ecology and evolution. Macroecologists study assemblages of differing species, whereas micro-evolutionary biologists study variants of heritable information within species, such as DNA and epigenetic modifications. These two different modes of variation are both driven by the same four basic processes, but app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…It can be utilised to describe variation at multiple levels of genetic organisation from single nucleotide polymorphisms (SNP), through whole species or larger taxonomic units to ecosystems. Due to its additive properties (Jost, 2007), the Shannon index has recently been postulated as a unifying measure for the partitioning of diversity at those levels (Gaggiotti et al, 2018;Sherwin, 2018). Additionally, Sherwin et al (2017) showed its potential utility in genomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…It can be utilised to describe variation at multiple levels of genetic organisation from single nucleotide polymorphisms (SNP), through whole species or larger taxonomic units to ecosystems. Due to its additive properties (Jost, 2007), the Shannon index has recently been postulated as a unifying measure for the partitioning of diversity at those levels (Gaggiotti et al, 2018;Sherwin, 2018). Additionally, Sherwin et al (2017) showed its potential utility in genomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Measures in the information theory, such as relative entropy, can be used to evaluate diachronic changes in language and to detect cognitive evolution (Sherwin 2018). The use of relative entropy as a measure of changes in the probability distribution over linguistic features has proven effective in many studies (Murdock et al 2017;Klingenstein et al 2014;Barron et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Entropy/information methods provide the added benefit that they can also be used to comprehensively characterize the physical world that interacts with biota [ 65 , 66 , 67 , 68 ].…”
Section: Shannon Entropy and Information: Processes In Ecologymentioning
confidence: 99%
“…Margalef’s championing of these methods in ecology also led to their uptake in the related field of evolution, where Shannon methods are regarded as one of the best ways of summarizing adaptive change [ 66 ]. A recent attempt at unifying the whole of ecology and evolutionary genetics minimized the mathematical basis [ 70 ], but it has recently been suggested that an entropy/information approach is ideal for this unification [ 5 , 65 , 66 , 67 , 68 ].…”
Section: Conclusion: Information Entropy and Margalef In Ecologmentioning
confidence: 99%